Building control practice on low cost housing / Mohd Kamal Hakimi Mohamad - Mohamad, Mohd Kamal Hakimi (Faculty of Architecture, Planning and Surveying, 2010)
The preparation of this dissertation was mainly motivated by the desire to provide an overview of facilities provided in low cost house flats in Shah Alam area. The primary aim of these studies is to highlight the standard guideline and requirement about facilities at low cost house flats that issue by MBSA. The second objective is to identify whether the provided facilities at all of the selected case studies are complied or not with the requirements. From the second objective, the third objective of this dissertation will be applied which to propose the best recommendation for better living at low cost house flats. This dissertation also includes the overview practice and scope of works of building control at local authority in Malaysia. The Shah Alam Local Authority had being chosen in completing this task. The interview session and the survey at case studies site is the methodology of study to collect the data information. The randomly of the residents at case studies site have been chosen to collect the information about their low cost house flats. After the data have been collected, the comparison of the facilities provided at all of case study have been made. The chart about the percentage of complying the requirements also given.